If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + 4x = 23 Solving 11 + 4x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 4x = 23 + -11 Combine like terms: 11 + -11 = 0 0 + 4x = 23 + -11 4x = 23 + -11 Combine like terms: 23 + -11 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| 7x+x=3x+6+5x | | 5n+3=-4 | | 18x=6x-35 | | 2(3x+1)=14-2x | | y=3x^2-30x+45 | | 5x-8+x=2(3x-8) | | -20=-4x-5x | | 42=4d-6d+6 | | 6y-7=2y+21-5y | | X-15=52 | | 4+9n+5=9 | | 2(2d+1)-3d=5(3d-2)+4d | | 2x^3=4x | | t^2+6t=-9 | | 5(2x+8)=-13+3 | | 0.3x-0.04(x+1)=3.04 | | 8(2n+5)=9(7n+3)+9 | | 8-3x=5x-10 | | -3(x-1)+9=10 | | 1-2(a+2)=9+a | | 20x+5y=1550 | | 27=-9(x+5) | | 7b+9=23 | | 18-c=11 | | 9x^2+12xy+4y^2= | | 9x=5x-12 | | -6-21=3p-12 | | 0.4(x+5)-0.3x=1 | | 3x-(x-3)=13 | | 8(x+7)=136 | | 12x=16x | | Y-16=-3 |